Early Diagnosis and Successful Treatment of Falciparum Malaria - Yaasiin, Putri Isa Maharani; Mahmudah, Iin Novita Nurhidayati (Universitas Muhammadiyah Surakarta, 2024)
Purpose: Malaria remains a major global health challenge, especially in tropical and subtropical regions such as Indonesia. Plasmodium falciparum, the most dangerous species, is associated with severe complications. This report highlights the importance of early detection, appropriate treatment, and increased public awareness in reducing malaria's impact. Methodology: This case involves a 34-year-old male patient who presented with high fever, weakness, muscle pain, and nausea for two months. The patient had a history of residing in Papua, a malaria-endemic area, and had been treated previously only with fever medication. Laboratory tests confirmed Plasmodium falciparum infection. The patient received antimalarial therapy and supportive care at PKU Muhammadiyah Surakarta Hospital. Results: Following treatment, the patient's condition improved within 24 days. The laboratory findings confirmed the presence of Plasmodium falciparum malaria, and the administration of the appropriate therapy led to recovery. Applications/Originality/Value: This case emphasizes the critical need for early detection and timely intervention in malaria treatment, particularly in endemic regions. It also highlights the significance of public health measures aimed at preventing the spread of malaria and increasing awareness of its symptoms and available treatments. Prompt and effective treatment can significantly reduce the severity and prevent complications of malaria, making early intervention key to managing this disease effectively.